A The Influence of Price Perception and Service Quality on IndiHome Customer Satisfaction in Surabaya: A Quantitative Study of Customer Satisfaction in Digital Subscription Services - Sulaicha; Hery Pudjoprastyono (Management Science Research Journal, 2026)
The rapid development of information and communication technology has transformed internet access into an essential necessity for supporting daily activities in modern society. As dependence on internet services increases, customer evaluations of price fairness and service quality have become critical determinants of satisfaction. Despite its dominant position as a fiber-optic internet service provider in Indonesia, IndiHome continues to face customer complaints related to pricing policies and service performance. This study aims to examine the effect of price perception and service quality on customer satisfaction among IndiHome subscribers in Surabaya. The research data were collected through an online questionnaire distributed to 120 respondents who had prior experience using IndiHome services and resided in Surabaya. A quantitative research approach was employed, and data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that price perception has a negative and significant effect on customer satisfaction, suggesting that unfavorable price perceptions reduce satisfaction levels. Conversely, service quality has a positive and significant effect on customer satisfaction, indicating that improvements in service responsiveness, reliability, and assurance can enhance customer satisfaction. The coefficient of determination (R²) value of 0.577 demonstrates that price perception and service quality jointly explain 57.7% of the variance in customer satisfaction. The findings contribute to the literature on consumer behavior in internet service industries by empirically confirming the contrasting roles of price perception and service quality in shaping customer satisfaction. Practically, this study implies that internet service providers should prioritize transparent pricing strategies and consistent service quality improvements to sustain customer satisfaction and long-term loyalty.